2022
DOI: 10.1038/s41598-022-13075-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bulk feed volume based on binocular stereo vision

Abstract: The volume detection of medical mice feed is crucial to understand the food intake requirements of mice at different growth stages and to grasp their growth, development, and health status. Aiming at the problem of volume calculation in the way of feed bulk in mice, a method for detecting the bulk volume of feed in mice based on binocular stereo vision was proposed. Firstly, the three-dimensional point coordinates of the feed's surface were calculated using the binocular stereo vision three-dimensional reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Studies have consistently shown a tendency for increased volumetric errors when estimating the volumes of smaller piles. For instance, Liu et al [68] focused on estimating the volumes of various small food piles, which had an average volume of 136,610 mm 3 (≈136.6 × 10 −6 m 3 ). Their estimations displayed an average error of 7%.…”
Section: Drone Photogrammetrymentioning
confidence: 99%
“…Studies have consistently shown a tendency for increased volumetric errors when estimating the volumes of smaller piles. For instance, Liu et al [68] focused on estimating the volumes of various small food piles, which had an average volume of 136,610 mm 3 (≈136.6 × 10 −6 m 3 ). Their estimations displayed an average error of 7%.…”
Section: Drone Photogrammetrymentioning
confidence: 99%
“…Yang [1] Proposed a matching descriptor based on the physical characteristics of sea waves to solve the matching difficulties caused by the texture similarity of sea surface images, and established the relationship between parallax and y coordinate to reduce the matching search range. Lu [2] and others applied binocular stereo photography to bed shape measurement, providing high-precision data and effective technical methods for studying the macro motion characteristics of bed shape under different boundary conditions. In view of the lack of obvious feature points in the wave image, Yang [3] Extracted feature points from the wave image to distinguish each point by integrating the four directions of wave size, shape, brightness, position and length, and completed the stereo matching of the tsunami warning system through the feature points and their features.…”
Section: Introductionmentioning
confidence: 99%